The efficiency of the patient fall prevention programme in selected medical institutions - Brabcová, Iva; Hajduchová, Hana; Tóthová, Valérie; Bártlová, Sylva; Doseděl, Martin; Malý, Josef; Kuběna, Aleš; Vlček, Jiří; Botíková, Andrea (Jihočeská univerzita v Českých Budějovicích, Zdravotně sociální fakulta, 2020)
Patient falls are frequent unwanted events. Hospital managements have the important task of implementing an efficient programme of patient fall prevention – which is complex, multifactorial and highly individualized. The goal of this research was to assess the efficiency of the implemented fall prevention programme in selected South-Bohemian hospitals. Methods: This is an epidemiological, observational and interventional study. In 2018, 16 departments in 4 South-Bohemian hospitals implemented the intervention programme – the aim of which was to minimize risk factors of patient falls. All patients were included in the programme during the monitored period at selected workplaces. In 2017, 24,379 patients were included, and in 2018 there were 25,773 patients. We then monitored the efficiency of the implemented interventions. We assessed the differences between the incidence of falls in 2017 before the implementation of the intervention programme and the incidence of falls in 2018 during the realization of the programme. The fall index was set to the number of falls of 1,000 patients and the number of fall injuries during 1,000 days in hospital. Results: After the implementation of the prevention programme, the decrease in the number of falls was recorded at the departments of subsequent and rehabilitation care (from 39.12 to 30.9 falls/1,000 patients and from 0.79 to 0.58 falls with injuries/1,000 hospital days), departments of surgery (from 5.88 to 5.78 falls/1,000 patients and from 0.98 to 0.59 falls with injuries/1,000 hospital days) and the department of psychiatry (from 14.27 to 7.48 falls/1,000 patients and from 0.58 to 0.23 falls with injuries/1,000 hospital days). On the contrary, a higher fall index of falls was confirmed at internal departments (from 8.54 to 10.4 falls/1,000 patients and from 1.22 to 1.63 falls with injuries/1,000 hospital days). Conclusions: The fall monitoring and the root analysis of their causes enable the managements of medical institutions to establish efficient remedial and preventative measures that decrease the incidence of falls and minimize their consequences.
Keywords: Falls; Index; Intervention; Patients; Prevention; Risk